EXPLORING MALAYSIAN TRADITIONAL POSTPARTUM CARE PRACTICES AMONG PRACTITIONERS - Adni Halianie Adnan; Hasif Rafidee Hasbollah; Dzulkifli Mukhtar; Adlina Azmi, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study explores traditional postpartum care practices among practitioners in Malaysia, focusing on techniques, dietary practices, and the role of education and certification in ensuring effective care. It aims to understand how these practices, deeply rooted in cultural and historical beliefs, contribute to maternal recovery during the postnatal period. The findings reveal that traditional practices, including hot stone compression, postpartum massage, body wrapping, vaginal steam baths, and herbal remedies, are widely utilized to promote healing and restore physical and mental health after childbirth. Dietary practices align with traditional beliefs emphasizing "hot" foods for recovery and modern approaches focusing on balanced nutrition. Practitioners' knowledge, often inherited or formally trained, plays a critical role in maintaining the efficacy and safety of these methods. Certifications such as SKM and DKM ensure professionalism, while modern adaptations like saunas offer safer alternatives to certain traditional techniques. Traditional postpartum care practices in Malaysia significantly aid maternal recovery by integrating cultural wisdom and modern healthcare standards. While these methods remain vital for physical and emotional well-being, further emphasis on formal training and safety enhancements can help sustain their relevance in contemporary healthcare settings. This study underscores the importance of blending tradition with innovation to improve maternal health outcomes.